'The naughty person': Exploring dynamic aspects of identity and children's discourses before and during the Libyan Uprising. (November 2016) - Barley, Ruth; Merchant, Guy
This article draws on data from an ethnography exploring young children's interactions in a multi-ethnic school in an urban area in the North of England. It focuses on the ways in which children explore and negotiate their identities against the shifting backdrop of local and global discourses about religion, race, gender and political change. In particular, we explore how children of the Libyan diaspora take up the semiotic resources available to them in their daily negotiations about identity. We show how through their spoken interactions, drawings and writings the children perform identities dialogically, with each other and with adult professionals, talking about salient issues of religious, cultural and national heritage before and during the Libyan Uprising in 2011. Using McFarlane's concept of 'translocal assemblages', we show how discourses and media narratives that circulate among diasporic communities provide a set of resources that children use to make sense of themselves in local contexts.